EVALUATING THE IMPACT OF CASE-BASED TEACHING MATERIALS IN PHYSICS TOWARDS OBE CURRICULUM - Mihardi, Satria; Derlina, Derlina; Bunawan, Wawan; Siregar, Alkhafi Maas; Hardianti, Tuti; Batubara, Muhammad Khairi Dahlan; Nawawi, Puji; Bintang, Andreas; Nurlita, Nurlita; Manik, Agnes Viola (Jurnal Curere, 2024)
Teaching materials play an essential role in education, serving as critical resources and guides for both teachers and students. They significantly enhance students' understanding and competency development by aligning with curriculum demands, particularly skill-based competencies. Science process skills are vital for engaging students in Physics, yet traditional teaching methods often limit the development of these skills. Effective Physics education should incorporate diverse strategies, including the case study approach, which fosters scientific thinking, creativity, and problem-solving skills. Implementing a scientific approach can further enhance these skills but may present challenges such as reduced learning pace and student interest. Teachers must address these challenges through close monitoring and thorough preparation, ensuring teaching materials are valid and effective. Researchers propose integrating case-based methods with a scientific approach to aid students in learning wave phenomena, making Physics concepts more accessible. The effectiveness of these materials will be evaluated using the N-Gain test, a statistical measure assessing improvement in student performance through a quasi-experimental pretest-posttest design, with data analyzed using SPSS. This study aims to identify issues and gather user feedback to optimize Physics teaching materials. The analysis of teaching materials developed using the case method, supported by a scientific approach, reveals their effectiveness in enhancing students' science process skills. The average N-Gain score of 0.71, reflects a 71% improvement, these materials significantly improve students' abilities, particularly in the Sound Wave subject. The effectiveness is evident in the enhanced skills of analysis and problem-solving among students, validated through pre-test and post-test comparisons. The average pre-test score was 60.4, which increased to 88.3 in the post-test. Despite some challenges such as inconsistent internet access, the teaching materials proved to be highly effective, with 20 students achieving effective results and 10 achieving fairly effective results. The teaching materials also foster various science process skills including critical thinking, experimentation, and communication. These methods encourage student engagement, critical thinking, collaboration, real-world application, creativity, and overcoming learning barriers, making education more dynamic and interactive.